Two new species of the South Asian catfish genus Pseudolaguvia from northeastern India (Teleostei: Sisoridae) - Tamang, Lakpa; Sinha, Bikramjit (Zootaxa, 2014)
Two new species of sisorid catfish, Pseudolaguvia magna and P. jiyaensis, are described from the upper Brahmaputra River basin in Arunachal Pradesh, northeastern India. Pseudolaguvia magna differs from its congeners by its much larger size (47.0 mm standard length vs. a maximum of 35.6 mm), by having a broader rhomboid thoracic adhesive apparatus, two pale-brown or cream patches on the mid-dorsal region across the dorsal midline: one rectangular to elliptic patch on the mid-interdorsal region, and another indistinct elliptic to irregular patch between the adipose and caudal-fins; and a small, round, pale-brown to cream spot on the lateral side of the head; and except for P. inornata, P. austrina, P. virgulata, and P. assula, in lacking pale to cream cross-bands on the body. Another syntopic new species, Pseudolaguvia jiyaensis, is distinguished from its congeners by having the thoracic adhesive apparatus almost reaching the pelvic-fin origin, and by having fewer vertebrae (25–27 vs. 28–34; except in P. tenebricosa and P. tuberculata). Details of the combination of characters differentiating each of the new species from its congeners are provided in the respective diagnoses.